2000
DOI: 10.1097/00001756-200009110-00014
|View full text |Cite
|
Sign up to set email alerts
|

Mossy fiber sprouting is dissociated from kindling of generalized seizures in the guinea-pig

Abstract: Controversy surrounds whether aberrant mossy fiber sprouting in the hippocampus is necessary for the establishment of seizure states. We investigated the association between mossy fiber sprouting and kindling in guinea-pigs, using either single-site or alternate-site stimulation. Kindling with single-site amygdaloid stimulation did not induce significant sprouting, despite the development of partial seizures. In contrast, single-site septal and alternating amygdaloid-septal stimulation produced moderate but si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…In experiments 4 and 5 we also examined mossy fiber sprouting using the Timm stain (Sloviter, 1991;Buckmaster and Dudek, 1997) and immunohistochemical staining for Met-enkephalin, neuropeptide Y, and synaptophysin (Table 2). Timm stain was performed with our routine protocol (Mohapel et al, 1997(Mohapel et al, , 2000Armitage et al, 1998). Immunohistochemical staining was performed using a conventional avidin -biotin -immunoperoxidase technique as described previously (Z hang et al, 1997, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments 4 and 5 we also examined mossy fiber sprouting using the Timm stain (Sloviter, 1991;Buckmaster and Dudek, 1997) and immunohistochemical staining for Met-enkephalin, neuropeptide Y, and synaptophysin (Table 2). Timm stain was performed with our routine protocol (Mohapel et al, 1997(Mohapel et al, , 2000Armitage et al, 1998). Immunohistochemical staining was performed using a conventional avidin -biotin -immunoperoxidase technique as described previously (Z hang et al, 1997, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some kainic acid (KA)-treated rats showing frequent SRS exhibit no detectable neuronal loss in the hippocampus (Sloviter, 1992;Buckmaster and Dudek, 1997). Numerous dissociations between epileptogenesis and mossy fiber sprouting have been described in the rat kindling and KA preparations of TLE (Elmer et al, 1997;Mohapel et al, 1997Mohapel et al, , 2000Armitage et al, 1998;Mello, 1998, 1999). In the present study we sought to test this hypothesis further, using both the traditional KA preparation of TLE in rats (Ben-Ari, 1985;Fisher, 1989;Sperk, 1994;Hellier et al, 1998) and a novel version of the preparation.…”
mentioning
confidence: 99%
“…Whether such severe, widely damaging, and often lethal seizures are at all comparable in severity to the antecedent insults experienced by most patients with temporal lobe epilepsy has not, to our knowledge, been addressed. Regardless, spontaneous seizures develop in severely brain-damaged animals whether or not hippocampal damage and synaptic reorganization occur (Sloviter, 1992;Elmer et al, 1997;Longo and Mello, 1998;Mohapel et al, 2000;Nissinen et al, 2001;Longo et al, 2002;Zhang et al, 2002). Because the development of spontaneous behavioral seizures does not necessarily indicate a damaged or hyperexcitable hippocampus (Sloviter, 1992) or any hippocampal involvement in the spontaneous seizures (Michalakis et al, 1998), electrophysiological studies in slices from hippocampi of epileptic animals in which the hippocampus has not been analyzed in vivo to verify principal cell hyperexcitability, nor anatomically to verify the presence of hippocampal sclerosis, seem of dubious value.…”
Section: Hippocampal Neuron Loss and Survival In Human Epilepsymentioning
confidence: 99%
“…Several previous studies have demonstrated kindling-induced morphological alterations at the cellular, dendritic, and synaptic level in the hippocampus (Armitage et al, 1998;Binder et al, 1999;Cavazos et al, 1994;Cavazos and Sutula, 1990;Geinisman et al, 1988Geinisman et al, , 1990Geinisman et al, , 1992Hawrylak et al, 1993;Hovorka et al, 1997;Jiang et al, 1998;Mohapel et al, 2000;Spiller and Racine, 1994;Sutula, 1990), amygdala (Nishizuka et al, 1991;Okada et al, 1993), and neocortex (Teskey et al, 1999(Teskey et al, , 2001. The two later studies that examined dendritic alterations in the neocortex following kindling focused on layer III pyramidal cells because earlier work had shown a sexual dimorphism at the structural level (Kolb and Stewart, 1991) and a differential plastic response to midline frontal lesions (Kolb and Whishaw, 1991) and gonadal hormones (Kolb and Stewart, 1995) in that layer.…”
Section: Introductionmentioning
confidence: 99%